Population characteristics of hostility among the population of a medium urban Siberian city: age and sex aspects - M. M. Kayumova; M. Yu. Akimov; V. V. Gafarov (Российский кардиологический журнал, 2020)
Aim. To assess age and sex characteristics of hostility among the population of a medium urban Siberian city.Material and methods. Cross-sectional epidemiological studies were carried out among men and women aged 25-64 years in Tyumen; the response rate was 85,0% among men and 70,3% among women. To assess hostility, the algorithms of the WHO program MONICA-Psychosocial were used. There were low, moderate and high levels of hostility. Low hostility was considered the population norm.Results. In the open population of a medium urban Siberian city, an unfavorable data was found for the hostility prevalence. High levels of hostility were revealed in both men and women in the whole age range. However, a high level of hostility prevailed among women compared to general population values by age and in four decades of life.Conclusion. The data obtained will help to develop evidence-based prevention programs based on the effects on psychosocial factors taking into account age and sex characteristics.